2018
DOI: 10.3390/molecules23113026
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum CQPC11 Isolated from Sichuan Pickled Cabbages Antagonizes d-galactose-Induced Oxidation and Aging in Mice

Abstract: Chinese pickled cabbage is a traditional fermented food that contains abundant microbes produced during the process of fermentation. In this work, an in vivo animal study was conducted to investigate the effects of a newly isolated lactic acid bacterium (Lactobacillus plantarum CQPC11, LP-CQPC11) on d-galactose-induced oxidation and aging in mice. Analysis of the serum and tissue samples of these mice using molecular biology approaches showed that LP-CQPC11 suppressed the decrease in thymus, brain, heart, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…From the mouse liver tissue measurement indicators GSH-Px and CAT (Table 5), vitamin C was as good as KSFY06-H in the antioxidant effect. Qian et al (2018) found that MDA activity in the serum and liver of antioxidized mice was decreased though L. plantarum CQPC-11 was administered. Wa et al (2019) found that probiotics significantly improved the antioxidant capacity of hyperlipidemic mice and increased the activity of antioxidant enzymes including SOD, GSH-PX, GPT, and GOT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…From the mouse liver tissue measurement indicators GSH-Px and CAT (Table 5), vitamin C was as good as KSFY06-H in the antioxidant effect. Qian et al (2018) found that MDA activity in the serum and liver of antioxidized mice was decreased though L. plantarum CQPC-11 was administered. Wa et al (2019) found that probiotics significantly improved the antioxidant capacity of hyperlipidemic mice and increased the activity of antioxidant enzymes including SOD, GSH-PX, GPT, and GOT.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the liver index of aging mice is significantly lower than that of normal nonaging mice (Sang et al, 2017). Therefore, changes in the structure and function of mouse organs can be ob- Skin, spleen, and liver can reflect some of the characteristic changes that occur in the body due to aging (Qian et al, 2018). The spleen is closely related to the cellular immune response of animals, but the immune ability of aging mice is relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal hormones, such as MTL and gas, exert direct influences on constipation, and the measurement of these indices can evaluate the degree of constipation [25,26]. MTL can improve stomach peristalsis, leading to the secretion of hydrochloric acid, pancreatic juice, and bile, which reflects gastrointestinal motility to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…An additional 5 L of distilled water was added to the final product residue, and it was re‐extracted at 80°C for 2 hr. The two filtrates were combined, the methanol was removed with a rotary evaporator, and the extracts were collected (Qian et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were divided into five groups. The experiment was conducted for 10 weeks (Figure 1), after which all of the mice were killed following a 24‐hr fast (Qian et al., 2018). Serum samples were obtained from the heart, and samples of the internal organs were excised for the experiment.…”
Section: Methodsmentioning
confidence: 99%